Structures of masonry walls in buildings of permanent ruin – causes of damage and methods of repairs - Szostak, Bartosz (Budownictwo i Architektura / Civil and Architectural Engineering, 2018)
Currently there is a lot of castles classified as objects of the permanent ruin. In according to conservation doctrine, it is needed to protect this objects and prevent further degradation. Usually one of the most destructed element in this type of object is masonry wall. In this article has been described selected types of the masonry walls of the permanent ruin, causes of their damages and repairs methods.